2015
DOI: 10.1113/ep085021
|View full text |Cite
|
Sign up to set email alerts
|

Chronic bilateral renal denervation reduces cardiac hypertrophic remodelling but not β‐adrenergic responsiveness in hypertensive type 1 diabetic rats

Abstract: New Findings r What is the central question of this study?Can bilateral renal denervation, an effective antihypertensive treatment in clinical and experimental studies, improve cardiac β-adrenoceptor responsiveness in a diabetic model with underlying hypertension? r What is the main finding and its importance?Bilateral renal denervation did not affect β-adrenergic responsiveness in the diabetic hypertensive rat heart, but denervation reduced the hypertension-induced concentric hypertrophic remodelling. This su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
1
7
0
2
Order By: Relevance
“…The hearts from the lean and obese animals of the Time‐Controls revealed that basal LVP dev declined over the 90 min between the start of the first and the start of the second ISO dose–response curve, but to a similar extent in both groups (lean −21 ± 5% versus obese −22 ± 6%, P > 0.05, Student's unpaired t test, n = 6 per group), which is comparable to previous reports (Bouwman et al., ; Thaung, Yao et al., ). The difference in normalized ISO dose–response curve between the hearts from the lean and obese rats remained in the Time‐Control group (data not shown).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The hearts from the lean and obese animals of the Time‐Controls revealed that basal LVP dev declined over the 90 min between the start of the first and the start of the second ISO dose–response curve, but to a similar extent in both groups (lean −21 ± 5% versus obese −22 ± 6%, P > 0.05, Student's unpaired t test, n = 6 per group), which is comparable to previous reports (Bouwman et al., ; Thaung, Yao et al., ). The difference in normalized ISO dose–response curve between the hearts from the lean and obese rats remained in the Time‐Control group (data not shown).…”
Section: Resultssupporting
confidence: 88%
“…Maximal LV developed pressure ( P max ) was determined with a postextrasystolic rest potentiation protocol, which consists of interposing trains of 20 Hz stimulation for 1, 2 or 4 s, followed by a 3 s rest period, after which normal 5 Hz pacing is resumed. The largest contraction immediately after the 3 s rest period reflects P max (Schouten, Allaart, & Westerhof, ; Thaung, Yao et al., ). At the end of the experiment, the isolated hearts of both groups were frozen in the presence or absence of CC.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study with SHRs, Jiang et al found that RD can significantly delay the progression of left ventricular hypertrophy, possibly not only through the suppression of sympathetic activity and attenuation of pressure load, but also due to the reduction in myocardial inflammation, as reflected by significantly reduced myocardial levels of Toll like receptor 4 (TLR4), nuclear factor kappa B (NF-κB), tumor necrotic factor alpha (TNF-α) and interleukin 6 (IL-6) after RD ( 22 , 31 ). In a subsequent study in hypertensive type 1 diabetic rats, Thaung et al found that bilateral RD reduces cardiac hypertrophic remodeling in these rats without restoring the attenuated cardiac β-AR responsiveness ( 32 ). Instead, they proposed that indirect cardiac effects, such as attenuation of sympathetic innervation of the systemic vasculature and/or kidney may be involved ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…release inflammatory cytokines into the systemic circulation, provoking myocardial damage. Renal injury is also indicated to increase sympathetic activity within the cardiovascular regulatory centres of the midbrain via the renal somatic afferent nerves, altering cardiac structure and function 16,17 . However, the existence of a clinical correlation between co-morbidities does not imply causality.…”
mentioning
confidence: 99%